1970
DOI: 10.1111/j.1476-5381.1970.tb10600.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral contraceptive steroids on bile secretion and bilirubin Tm in rats

Abstract: Summary1. The effect of oestrogens and progestogens and their 17a-ethinyl derivatives on bile flow, maximum rate of bilirubin secretion, serum and liver bilirubin has been studied. 2. Both 17a-ethinyl substituted oestrogens and progestogens greatly reduced the basal bile flow. The parent compounds, oestradiol-17f3 and 19-nortestosterone had little or no effect. 3. A much larger dose of progestogens (40 mg/kg) than oestrogens (5 mg/kg) was needed. 4. Between 12 and 48 h were required for 17a-ethinyloestradiol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…21 However, many researchers found increased Alkaline phosphatase levels in OCP users. These results are compatible with Ekhator 20 , KATZ, et al 13 , Hargreaves 23 , Dickerson, et al 15 , and Larsson-Cohn et al 17 . The increased ALP level could be described by cellular degeneration of myocardial, neuronal, and liver cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…21 However, many researchers found increased Alkaline phosphatase levels in OCP users. These results are compatible with Ekhator 20 , KATZ, et al 13 , Hargreaves 23 , Dickerson, et al 15 , and Larsson-Cohn et al 17 . The increased ALP level could be described by cellular degeneration of myocardial, neuronal, and liver cells.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, serum total bilirubin levels are higher in OCP users in comparison to non-OCP users. This observation coincides with Osifo 13 , KATZ 14 , Dickerson, et al 15 , Rahim et al 16 , and Heikel and Lathe 17 . Larsson Cohn et al 18 observed that serum bilirubin level was within the standard limit after taking OCP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…EE administration not only decreases bile salt transport but also decreases the secretory maxima for other organic anions which utilize separate transport pathways. For example, BSP and bilirubin transport maximum are reduced by approximately 50% (21,53,55,58). This generalized defect in organic anion transport suggests a major abnormality in the canalicular membrane; however, no studies have been published which examine hepatic uptake, i.e., sinusoidal membrane integrity.…”
mentioning
confidence: 99%
“…The causes(s) of bile secretorv failure (cholestasis) is unknown, but these agents have focused attentioIn oIn abnormalities in the hepatocyte. Ethinyl estradiol, a synthetic estrogen, has been extensively studiedl as a dcrug whiclh produces bile secretory failure characterized by (lecreases in the bile salt independent component of bile flow (2)(3)(4), the maximumti capacity to excrete organic anions such as bile acids (5), bilirubin (6), and bromosulfophthalein (4, 7) and decreased hepatic Na+-K+-ATPase activity (8,9). It has been suggested that this diffuse abnormality in biliary secretory processes is primarily the result of changes in membrane lipid structure (9).…”
Section: Introductionmentioning
confidence: 99%